THE EFFECT OF CAPITAL STRUCTURE, COMPANY GROWTH, AND PROFITABILITY ON FIRM VALUE WITH DIVIDEND POLICY AS A MODERATING VARIABLE - Salsabila Vidyawati; Anak Agung Gede Suarjaya (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Firm value in the capital market is reflected in stock prices, which represent investors' perceptions of a company's success and performance. This study aims to examine the effect of capital structure, company growth, and profitability on firm value, as well as the moderating role of dividend policy. The data used are secondary data in the form of financial statements of manufacturing sector companies obtained from the official website of the Indonesia Stock Exchange (www.idx.com) for the 2021–2023 period. Out of 65 companies, 56 were selected as samples using simple random sampling. The analytical method employed is Moderated Regression Analysis (MRA). The results indicate that capital structure has a negative and significant effect on firm value, company growth has a positive and significant effect, and profitability has a negative and significant effect. Furthermore, dividend policy is found to strengthen the influence of capital structure and profitability on firm value, while weakening the effect of company growth on firm value. These findings highlight the importance of effective capital structure management, growth strategies, and appropriate dividend policies in enhancing firm value from the investors’ perspective.